2011
DOI: 10.3201/eid1709.102022
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic (H1N1) 2009 and Seasonal Influenza among Children, Israel

Abstract: During the pandemic (H1N1) 2009 outbreak in Israel, incidence rates among children were 2× higher than that of the previous 4 influenza seasons; hospitalization rates were 5× higher. Children hospitalized for pandemic (H1N1) 2009 were older and had more underlying chronic diseases than those hospitalized for seasonal influenza.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…The virus was detected once again only in October 2010 and co‐circulated with other influenza viruses during the next winter season. During the pandemic period, morbidity rates based on visits to community clinics due to ILI were followed by the ICDC 5, 12. Figure 1 shows the age‐related dynamics of the morbidity which peaked in August, September, and November of 2009.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The virus was detected once again only in October 2010 and co‐circulated with other influenza viruses during the next winter season. During the pandemic period, morbidity rates based on visits to community clinics due to ILI were followed by the ICDC 5, 12. Figure 1 shows the age‐related dynamics of the morbidity which peaked in August, September, and November of 2009.…”
Section: Resultsmentioning
confidence: 99%
“…Local circulation was monitored by an enhanced surveillance system based on records of visits to primary physicians due to influenza‐like illness (ILI) and on laboratory results of respiratory samples taken from ILI patients in sentinel clinics 4, 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Of the few pandemic studies which mentioned no additional interventions, one suggested an effect of school closures: in Israel in 2009, three waves of infection corresponded to the planned closure and reopening of schools. 60 In the England and Wales data for the 2009 pandemic, other interventions (vaccination and antivirals) were used to only a limited extent; incidence still clearly declined during the school summer holiday and increased afterwards. 28 Some studies of seasonal influenza mentioned additional interventions (eg, vaccination, 61-63 prophylactic amantadine, 64 hygiene promotion, 37 40 65 closure of public places 37 and advice to avoid large gatherings 43 ).…”
Section: Use Of Multiple Interventionsmentioning
confidence: 99%
“…Other studies comparing pandemic influenza with previous seasons have found that children admitted with influenza A(H1N1)pdm09 were older than those admitted with seasonal influenza A in the years prior to the pandemic [3,7,8,26,[30][31][32][33]. Apart from age, no other differences were found in hospitalized and PICU cases during the pandemic period and the 2010/2011 season.…”
Section: Discussionmentioning
confidence: 99%